Palaearctic Protosmia bees of the subgenus Chelostomopsis (Megachilidae, Osmiini): biology, taxonomy and key to species - Müller, Andreas (Zootaxa, 2017)
Chelostomopsis represents a subgenus of the osmiine bee genus Protosmia (Megachilidae) containing three Palaearctic and one Nearctic species. Analysis of female pollen loads and literature data indicate that all Chelostomopsis species are broad pollen generalists exploiting the flowers of numerous plant families, such as Fabaceae, Asteraceae, Lamiaceae, Cistaceae and Brassicaceae. Preexisting linear cavities in dead wood or pine cones serve as nesting sites and pure resin is used to construct cell partitions and nest plug. The taxonomic revision of the Palaearctic P. (Chelostomopsis) species revealed the existence of a still undescribed species from the Levant, Protosmia (Chelostomopsis) angustimandibulae spec. nov. Keys for the identification of the three Palaearctic P. (Chelostomopsis) species are given.